Long Absence from Work Due to Sickness among Psychiatric Out¬patients in Japan, with Reference to a Recent Trend for Perfec¬tionism - K Nakamura; H Seto; S Okino; K Ono; M Ogasawara; Y Shibamoto; T Agata; K Nakayama (Tehran University of Medical Sciences, 2012)
Background: Sick leave from work due to psychiatric disorders is a major public health problem, not only in Japan but also worldwide. As males and females in Japan tend to differ in their approach to work, a gender difference in perfectionism might be expected. We investigated the background factors leading to long-term absence from work due to sickness among psychiatric outpatients in Japan.    Methods: We surveyed 73 psychiatric outpatients who were absent from work for a long time (POAWs) and 228 employees without long-term sickness absence as controls. GHQ-30, NEO-FFI, MPS, RSS and questionnaires inquiring about background factors, including relationships with others, was used, and the data were compared between males and females. Results: Male POAWs had a significantly higher tendency for depression and perfectionism than the controls, but in females this difference was not significant. With regard to personal relationships of POAWs, males had worse relationships with superiors and colleagues, whereas females had worse relationships with superiors, colleagues, and family. Conclusions: The data suggested that male workers exhibiting perfectionism tend to undertake too much work and become exhausted when trying to cope with complex human relationships in the workplace. Female workers having the double burden of family commitment and perfectionism tend to be isolated in terms of personal relationships, leading to exhaustion both in and outside the workplace.